Shadow Globalization, Ethnic Conflict And New Wars : A Political Economy of Intra-State War (Routledge, 2003)
Focusing on the political economy of so-called new wars, this book presents a series of studies that analyse the complexities of current warfare by moving from the global sphere to local spots of organised violence. It thus raises questions about the very idea of intra-state wars and shows that these wars are inseparably linked to the global economy and the world political order. In this way, this study also offes a unique contribution to understanding the post-September 11 world. This will be topical and controversial reading for students and scholars of international relations and international political economy, as well as experts in foreign policy, peace and conflict studies.